The Purchasing Power Parity Criterion for Stabilizing Exchange Rates. (IMF Working Papers; Working Paper, 1989)
The use of purchasing power parity as a basis of fixing exchange rates among industrial countries, as proposed by McKinnon, is discussed and contrasted with alternative interpretations of the PPP doctrine. Major policy implications of such a regime are emphasized. Furthermore, a new technique for estimating PPP exchange rates which makes use of price pressure exerted by exchange deviation is introduced. This method is capable of solving the 'base-year' problem more satisfactorily than the traditional Cassel-Keynes methodology. Estimated yen/dollar and mark/dollar PPP exchange rates are close to estimates derived using other methods.